An Overview of Comparative Analysis of Bibliometric Analysis and Scientific Mapping in Literature Review - Burkut, Emine Banu (Akademisyen Yayınevi Kitabevi, 2025)
Bibliometric analysis has emerged as a critical tool in the field of architecture, offering a systematic and quantitative approach to understanding the evolution, trends, and impact of academic research. As the architectural discipline continues to expand, incorporating interdisciplinary approaches and addressing global challenges such as sustainability, urbanization, and technological innovation, bibliometric analysis provides valuable insights into the dynamics of scholarly communication and knowledge production.